Prognostic and clinicopathological value of the controlling nutritional status score in patients with multiple myeloma: a meta-analysis - Jin, Yin; Gu, Wenfei (Frontiers in Oncology, 2025)
BackgroundThe effect of the controlling nutritional status (CONUT) score on forecasting multiple myeloma (MM) prognosis is previously analyzed, whereas the results remained inconsistent. The present meta-analysis focused on identifying the exact function of CONUT in forecasting MM prognosis.MethodsWeb of Science, PubMed, Embase, CNKI, and Cochrane Library were comprehensively searched between inception and 1 February 2025. The effect of CONUT on forecasting MM overall survival (OS) and progression-free survival (PFS) was determined by computing pooled hazard ratios (HRs) together with 95% confidence intervals (CIs).ResultsThere were nine studies with 1,176 patients being recruited into the present work. As indicated by our pooled data, elevated CONUT was related to the dismal OS (HR = 1.87, 95% CI = 1.37–2.54, p < 0.001) of patients with MM. Nonetheless, CONUT was not significantly related to PFS (HR = 1.33, 95% CI = 0.81–2.19, p = 0.254) of MM. Furthermore, higher CONUT score showed a significant relationship to bone marrow plasma cells >30% (OR = 2.30, 95% CI = 1.32–3.99, p = 0.003). On the other hand, CONUT was not markedly correlated with gender (OR = 2.68, 95% CI = 0.81–8.82, p = 0.105), ISS stage (OR = 1.28, 95% CI = 0.94–1.75, p = 0.119), or ECOG PS (OR = 1.30, 95% CI = 0.84–2.01, p = 0.234) of MM.ConclusionCollectively, according to our results in this meta-analysis, higher CONUT score is markedly related to dismal OS, but not PFS in patients with MM. CONUT score can be used as a candidate marker used to predict MM prognosis in the clinic in the future.